Facilitation of information literacy through a multilingual MOOC considering cultural aspects. Issue 3 (23rd December 2020) - Dreisiebner, Stefan; Polzer, Anna Katharina; Robinson, Lyn; Libbrecht, Paul; Boté-Vericad, Juan-José; Urbano, Cristóbal; Mandl, Thomas; Vilar, Polona; Žumer, Maja; Juric, Mate; Pehar, Franjo; Stričević, Ivanka
Abstract : Purpose: The purpose of this paper is to demonstrate the rationale, technical framework, content creation workflow and evaluation for a multilingual massive open online course (MOOC) to facilitate information literacy (IL) considering cultural aspects. Design/methodology/approach: A good practice analysis built the basis for the technical and content framework. The evaluation approach consisted of three phases: first, the students were asked to fill out a short self-assessment questionnaire and a shortened adapted version of a standardized IL test. Second, they completed the full version of the IL MOOC. Third, they were asked to fill out the full version of a standardized IL test and a user experience questionnaire. Findings: The results show that first the designed workflow was suitable in practice and led to the implementation of a full-grown MOOC. Second, the implementation itself provides implications for future projects developing multilingual educational resources. Third, the evaluation results show that participants achieved significantly higher results in a standardized IL test after attending the MOOC as mandatory coursework. Variations between the different student groups in the participating countries were observed. Fourth, self-motivation to complete the MOOC showed to be a challenge for students asked to attend the MOOC as nonmandatory out-of-classroom task. It seems that multilingual facilitation alone is not sufficient to increase active MOOC participation. Originality/value: This paper presents an innovative approach of developing multilingual IL teaching resources and is one of the first works to evaluate the impact of an IL MOOC on learners' experience and learning outcomes in an international evaluation study.